James Joyce's A Little Cloud: The Construction and Resistance of the Postcolonial City - Asri, Zietha Arlamanda (Vivid: Journal of Language and Literature, 2025)
This research aims to analyse the construction of urban space in the short story "A Little Cloud" by James Joyce through a postcolonial perspective. This short story describes how the character Little Chandler and his family experience dislocation and discrimination in London, which was initially expected to be a utopian city with economic progress and industrialisation. This research uses postcolonialism theory and Sara Upstone's concept of urban space to identify how London's urban space became a colonial space that maintained the stability of colonialism through boundaries constructed to distinguish between the English and the Irish. The results show the ambiguity between the idea of utopia and dystopia in London's urban space and the resistance strategies used by the characters in the short stories to deal with pressure and oppression. These resistance strategies include displacement and carnivalization of identity in public spaces. This research also highlights how the depiction of the city in postcolonial literature questions the city's position as a friendly space for all people, including minorities and migrants, and whether there is a repetition of the relationship between the coloniser and the colonised.